The Impact of Native and Foreign Languages on the Linguistic Identity Formation of Kazakhstani Youth - Baimyrza, Ainur; Akkuzov, Abdyzhalil; Kaiyrbekova, Ulbossyn; Akmaral Kurmanayeva; Aizhan Serikbayeva (Forum for Linguistic Studies, 2024)
This article delves into the influence of native and foreign languages on the linguistic identity of Kazakhstani youth. The primary focus is on analyzing the perception and utilization of languages among young people in Kazakhstan, exploring how these factors impact their self-identification and cultural affiliation. To gather comprehensive empirical data, an extensive experiment was conducted involving both survey and semi-structured interviews. The results of the study revealed that the knowledge and use of foreign languages, alongside the native language, significantly shape the linguistic identity of the youth. The findings underscore the dual importance of preserving the native language while simultaneously embracing foreign languages, which collectively contribute to the development of a rich, multicultural, and multilingual identity. This balance is crucial for fostering a well-rounded and inclusive linguistic environment in Kazakhstan.